2001
DOI: 10.1038/sj.bmt.1703026
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble adhesion molecules in stem cell transplantation-related complications

Abstract: Summary:To assess the involvement of vascular endothelial cell activation and damage in stem cell transplantation (SCT)-related complications, such as acute and chronic GVHD and thrombotic microangiopathy (TMA), we investigated the changes in serum levels of soluble forms of vascular cell adhesion molecule-1 (sVCAM-1) and Eselectin (sE-selectin) in SCT. The soluble form of intercellular adhesion molecule-1 (sICAM-1) was also analyzed. In patients with acute GVHD (grades II-IV), serum levels of sE-selectin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 31 publications
2
48
0
1
Order By: Relevance
“…9 In line with the cited report, we found that maximal VCAM-1 release into patients' serum in the first 100 days post SCT correlated with GvHD (P ¼ 0.03; data not shown), suggesting that, indeed, serum analyses not only reflect damage but also allow activation of endothelial cells.…”
supporting
confidence: 79%
“…9 In line with the cited report, we found that maximal VCAM-1 release into patients' serum in the first 100 days post SCT correlated with GvHD (P ¼ 0.03; data not shown), suggesting that, indeed, serum analyses not only reflect damage but also allow activation of endothelial cells.…”
supporting
confidence: 79%
“…3,12 Patients meeting criteria of TAM but without aGvHD were more likely to have received grafts with major or bidirectional ABO blood group barrier (Po0.025), further supporting this hypothesis. Increased soluble vascular cell adhesion molecules reported in GvHD and TAM 41 as markers of endothelial damage may represent a common pathophysiologic pathway. Elevated number of circulating endothelial cells may be useful for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…To further test these hypotheses, measures of endothelial damage may be helpful. 2,3,41 Plasma exchange has been used extensively to treat TAM but is now not considered to be effective. Plasma exchange is used in classical TTP and this use is in accordance with today's understanding of its pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Takatsura et al 23 did not observe any impact of TBI on VWF and TM levels. Matsuda et al 24 investigated the serum levels of sVCAM-1, sE-selectin and sICAM-1 in HSCT, excluding patients with severe infections. They showed that all soluble adhesion molecules increased after HSCT (day þ 30) and that levels were higher after allo-compared with auto-HSCT.…”
Section: Soluble Markers and Adhesion Moleculesmentioning
confidence: 99%